2018
DOI: 10.1177/1357633x18800211
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a novel, automated telephone intervention on time to hospitalisation in patients with COPD: A randomised controlled trial

Abstract: Introduction Owing to its capacity to perform remote assessments, telemedicine is rising as a new force in chronic obstructive pulmonary disease (COPD) management. We conducted an eight month randomised-controlled-trial to study the effect of an automated telemedicine intervention on patients’ time-to-hospitalisation. Methods A total of 168 patients with a diagnosis of COPD in the past 24 months were enrolled to receive the intervention at a primary care clinic. The treatment group received daily phone message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
0
17
0
4
Order By: Relevance
“…Two reported an increase in hospital admissions in the RPM group; 41 42 Witt Udsen et al 42 had the largest sample size (n=578/647 intervention/ control) of the trials. Across the RCTs, COPD-related hospitalisations differed from a mean difference of 10 fewer admissions in the intervention group of Sink et al 43 over 8 months (absolute risk reduction=11.6%; RPM=6 hospitalisations vs non-monitored=16 hospitalisations) to a slight increase in admissions over a 6-month period (RPM admissions=0.63 vs 0.32 in non-monitored mean difference: 0.32, p value: 0.026). 41 All cohort studies (n=9) reported a reduction in at least one measure of acute hospital use.…”
Section: Cvd Non-invasivementioning
confidence: 80%
“…Two reported an increase in hospital admissions in the RPM group; 41 42 Witt Udsen et al 42 had the largest sample size (n=578/647 intervention/ control) of the trials. Across the RCTs, COPD-related hospitalisations differed from a mean difference of 10 fewer admissions in the intervention group of Sink et al 43 over 8 months (absolute risk reduction=11.6%; RPM=6 hospitalisations vs non-monitored=16 hospitalisations) to a slight increase in admissions over a 6-month period (RPM admissions=0.63 vs 0.32 in non-monitored mean difference: 0.32, p value: 0.026). 41 All cohort studies (n=9) reported a reduction in at least one measure of acute hospital use.…”
Section: Cvd Non-invasivementioning
confidence: 80%
“…In an RCT with a different design, Sink et al [ 25 ] recruited 168 COPD patients with mild to very severe airflow obstruction. Patients allocated to the treatment group received a daily message regarding their breathing status.…”
Section: Studies With Positive Resultsmentioning
confidence: 99%
“…The time to hospitalization was significantly different between the two groups, favoring the TM group (hazard ratio 2.36, 95% CI: 1.02–5.45; p = 0.043), while the same applied for the number of hospital admissions. The positive results were associated with the early intervention and proper consultation by the health staff, leading to the prompt detection and treatment of AECOPDs and finally to the reduction in hospital admissions [ 25 ].…”
Section: Studies With Positive Resultsmentioning
confidence: 99%
“…Seventeen [ 19 35 ] of the 19 studies [ 19 38 ] compared remote home monitoring (RHM) to ‘no remote home monitoring’ (no RHM), and two [ 36 , 37 ] compared RHM with provider’s feedback to RHM without feedback. The 19 studies were conducted between 2006 and 2018 and had sample sizes ranging from 34 to 1,238 patients (details of participants' characteristics included in the studies are presented in online supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 19 22 , 25 , 26 , 30 , 32 , 34 , 35 ] recruited patients from multiple centres, and one [ 21 ] spanned five European countries (Spain, the United Kingdom, Slovenia, Estonia and Sweden). The remaining eighteen studies were conducted in Australia (2) [ 24 , 27 ], Canada (1) [ 30 ], Denmark (1) [ 32 ], Germany (2) [ 28 , 37 ], Hong Kong (1) [ 31 ], Italy (1) [ 25 ], Netherlands (3) [ 20 , 22 , 23 ], South Korea (1) [ 19 ], Spain (2) [ 26 , 29 ], the United Kingdom (1) [ 33 ], and the United States (3) [ 34 36 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%